Shell catalysts for producing alkenyl carboxylates with improved Pd distribution

The asymmetric Gaussian distribution of Pd in a shell catalyst, achieved through controlled application in a fluidized bed, addresses the distribution issues of Pd and Au catalysts, enhancing catalytic performance in vinyl acetate monomer production.

JP2024545957AActive Publication Date: 2024-12-16CLARIANT INT LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024536160
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-21
Filing Date
2022-12-09
Publication Date
2024-12-16
Estimated Expiration
2042-12-09

AI Technical Summary

Technical Problem

Existing Pd and Au containing shell catalysts exhibit unfavorable distribution of catalytically active species, leading to reduced catalytic effectiveness in processes like vinyl acetate monomer production.

Method used

A shell catalyst with an asymmetric Gaussian distribution of Pd, characterized by a maximum concentration within 0 to 40 micrometers from the surface and a half-width of 10 to 70 micrometers, is achieved through controlled application of Pd and Au precursor compounds in a fluidized bed recirculation process, with temperature adjustments to limit diffusion into the catalyst support.

Benefits of technology

The improved Pd distribution results in enhanced catalytic performance, demonstrated by higher activity, selectivity, and yield in the production of vinyl acetate monomer, surpassing conventional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024545957000001_ABST
    Figure 2024545957000001_ABST
Patent Text Reader

Abstract

The present invention relates to a shell catalyst comprising Pd and Au, characterized by improved Pd distribution, and also to two processes for producing said catalyst, and a process for producing vinyl acetate monomer using said catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a shell catalyst comprising Pd and Au, characterized by an improved distribution of Pd. The present invention also relates to two processes for the preparation of this catalyst, and to a process for the preparation of vinyl acetate monomer using this catalyst. [Background technology]

[0002] Shell catalysts have been used for many years in various catalytic processes. They are characterized in that the catalytically active species are not distributed throughout the entire catalyst support, but only in a shell region around the center of the catalyst support.

[0003] One application area is the production of vinyl acetate monomer (VAM) by the reaction of ethylene, acetic acid and oxygen. Shell catalysts containing Pd and Au compounds as catalytically active species, which may also contain various promoters, are widely used here.

[0004] Thus, WO2008 / 145388A1 describes the preparation of Pd-containing shell catalysts and Au-containing shell catalysts, in which the application of catalytically active species is carried out by spray impregnation of a fluidized bed of a catalyst support. The resulting shell-like regions of catalytically active species have an approximately constant distribution of catalytically active species.

[0005] In WO2005 / 065821A1, the pore structure of the catalyst support is supported by absorption of a solution containing catalytically active species. Alternatively, a mixture of catalytically active species and a binder material is applied to the surface of the catalyst support. The distribution of the catalytically active species is unfavorable because it either spreads deep inside the support or results in an outer layer with a very uniform distribution over a relatively large area of ​​this applied shell. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] WO2008 / 145388A1 [Patent Document 2] WO2005 / 065821A1 Summary of the Invention [Problem to be solved by the invention]

[0007] Pd and Au-containing shell catalysts featuring improved Pd concentration are still sought for improved catalytic efficiency. [Means for solving the problem]

[0008] This object is achieved by a shell catalyst comprising Pd and Au, in which the concentration profile of palladium in the shell catalyst conforms to an asymmetric Gaussian distribution, the maximum value of the palladium concentration is within a range of 0 to 40 micrometers from the geometric surface of the catalyst molding, the palladium is present in a region of a shell thickness of 30 to 200 μm, the half-width of the concentration distribution is 10 to 70 μm, and the asymmetry of the Gaussian distribution is characterized in that the ratio of the value on the left side of the half-width to the value on the right side of the half-width is 0.05 to 0.55.

[0009] The present invention further provides a first method for producing the shell catalyst according to the present invention, the first method comprising the steps of: (a) subjecting a catalyst support bed to a recirculating operation and heating said bed during the recirculating operation to a temperature of from 60°C to 120°C; (b) applying dissolved Pd-containing precursor compound and dissolved Au-containing precursor compound to the recirculating catalyst support bed either continuously or simultaneously by spraying, where in the case of simultaneous application the temperature is 5° C. to 30° C., preferably 7° C. to 25° C., most preferably 10° C. to 20° C. lower than that in step (a), and in the case of sequential application the temperature of the first application is 5° C. to 30° C., preferably 7° C. to 25° C., most preferably 10° C. to 20° C. lower than that in step (a).

[0010] The catalyst according to the present invention can also be produced by a second production method according to the present invention. The second production method comprises the following steps: (a) operating a catalyst support bed in a recirculating manner and contacting the bed with water by spraying at a temperature in the range of 55°C to 110°C; (b) spraying the dissolved Pd-containing precursor compound and the dissolved Au-containing precursor compound onto the recirculating catalyst support bed either sequentially or simultaneously, where if simultaneous, the temperature is the same as in step (a), and where if sequential, the temperature of the first application is the same as in step (a). Effect of the Invention

[0011] Surprisingly, it has been found that the method according to the invention makes it possible to produce shell catalysts with an improved Pd distribution inside the individual catalyst bodies, the Pd concentration distribution having the form of an asymmetric Gaussian distribution, the maximum value of the Pd concentration being located in the range of 0 to 40 micrometers from the surface of the catalyst body, the palladium being present in a region of the shell thickness of 30 to 200 μm, the half-width of the concentration distribution being 10 to 70 μm, and the asymmetry of the Gaussian distribution being characterized in that the ratio of the value on the left side of the half-width to the value on the right side of the half-width is 0.05 to 0.55. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 shows, for example catalyst 1, a plot of the experimental data points of Pd concentration and the sigmoid function determined by the same measurement method that determined the start of the geometric surface after measuring the xsurface. [Diagram 2] FIG. 2 shows a plot of the experimental data points of Pd concentration and the curve for catalyst 1 obtained using an appropriate fit function in the examples. [Diagram 3] FIG. 3 shows a plot of the experimental data points of Pd concentration and the curve for catalyst 2 obtained using an appropriate fit function in the examples. [Figure 4]FIG. 4 shows a plot of the experimental data points of Pd concentration and the curve for catalyst 3 obtained using an appropriate fit function in the examples. [Diagram 5] FIG. 5 shows the curves for catalysts 1, 2 and 3 obtained in the examples using appropriate fitting functions. [Figure 6] FIG. 6 shows the selectivity at different space-time yields and their trend line plots for catalysts 1 and 2 in the reaction of acetic acid, ethylene and oxygen to obtain vinyl acetate monomer in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In the present specification, a shell catalyst means a catalytic body containing Pd and Au, in which the Pd and Au compounds are present as catalytically active species in the outer region of the support, forming a so-called shell, and the interior of the catalytic body is substantially free of Pd and Au compounds, which shell usually exhibits a high concentration of catalytically active species in a shallow region of the catalytic body.

[0014] For both of the processes according to the invention, the shell catalyst is in the form of a shaped catalyst body after step (b), which previously involved a catalyst support.

[0015] The maximum value of the Pd concentration in the shell catalyst lies in each case within a range of 0 to 40 micrometers, preferably 5 to 40 micrometers, preferably 5 to 35 micrometers, particularly preferably 5 to 30 micrometers from the geometric surface of the catalyst shaped body.

[0016] The shell catalyst comprises a Pd-containing shell having a thickness of 30 to 200 micrometers, preferably 40 to 180 micrometers, particularly preferably 50 to 160 micrometers, and most preferably 60 to 140 micrometers.

[0017] In one embodiment, the shell catalyst has a Pd concentration profile with a half-width in the range of 45 to 65 μm. In one embodiment, the shell catalyst has a Pd concentration profile with an asymmetric Gaussian distribution, with the ratio of the value on the left side of the half-width to the value on the right side of the half-width being in the range of 0.05 to 0.55, preferably in the range of 0.05 to 0.45, and particularly preferably in the range of 0.05 to 0.35.

[0018] The recirculating operation of the catalyst support bed is usually carried out using suitable fluidized bed equipment. Such equipment is sold by Glatt GmbH (Binsen, Germany), Aeromatic-Fielder AG (Büdendorf, Switzerland), FluidAirInc (Aurora, Illinois, USA), Huettlin GmbH (Steinen, Germany), UmangPharmatechLtd. (Maharashtra, Germany) and RomacoPharmatechnikGmbH (Karlsruhe, Germany). Particularly preferred fluidized bed equipment for carrying out the process according to the invention is sold by RomacoPharmatechnikGmbH under the trade names Innojet® Ventilus or Innojet® AirCoater. These equipments comprise a cylindrical vessel with a stationary and fixed vessel bottom, in the center of which the spray nozzle is attached. The bottom consists of circular vanes mounted one above the other in stages. Process air flows horizontally and into the vessel between the individual vanes with an outward circumferential flow component toward the vessel wall.

[0019] This creates a so-called sliding air layer, where the shaped catalyst supports are initially carried outward towards the vessel wall. On the outer vessel wall, vertically directed process air is provided which directs the catalyst supports upwards. When the catalyst supports reach the top end, they return on a path tangential to the centre of the base, passing through the spray mist of the nozzles in the process. After passing through the spray mist, the process starts again. The management of the process air provides the basis for a substantially homogeneous, toroidal fluidised bed-like recirculating operation of the catalyst supports.

[0020] In the process according to the invention, it is preferred to create a fluidized bed in which the recirculating compacts move along an elliptical or toroidal path. In the prior art, the point at which the bed particles transition to a completely free-moving state (fluidized bed) is called the minimum fluidization point and the associated fluid velocity is called the minimum fluidization velocity.

[0021] In the process according to the invention, preferably the fluid velocity is up to four times the minimum fluidization velocity, preferably up to three times the minimum fluidization velocity, more preferably up to two times the minimum fluidization velocity.

[0022] In the manufacturing method according to the invention, the catalyst support is recirculated in the fluidized bed along an elliptical or toroidal path, preferably a toroidal path. According to the invention, "elliptical recirculation" means that the catalyst support in the fluidized bed moves on an elliptical path in the vertical plane, the first and second axes of which have different sizes. In the case of "toroidal recirculation", the catalyst support in the fluidized bed moves on an elliptical path in the vertical plane, the first and second axes of which have different sizes, and on a circular path in the horizontal plane, the radii of which have different sizes.

[0023] On average, in the case of "elliptical recirculation", the catalyst support moves on an elliptical path in a vertical plane, and in the case of "toroidal recirculation", the catalyst support moves on a toroidal path, i.e., the catalyst support moves in a spiral manner along the surface of a torus having a vertical elliptical cross section.

[0024] In one embodiment, prior to application of the Pd-containing precursor compound and the Au-containing precursor compound, an acetate is applied to the catalyst support. This is preferably done using a solution containing an acetate. The solvent used to prepare the solution is preferably water, more preferably deionized water. The acetate used is typically an alkali metal acetate, preferably potassium acetate.

[0025] Application of the acetate containing solution can be done by any method known in the art, such as wet chemical impregnation, pore filling method (incipient wetness), and any type of spray impregnation.

[0026] The application of acetate is preferably carried out before step a) of the production method according to the invention.

[0027] When the acetate is in the form of an alkali metal acetate, the amount of alkali metal added is in the appropriate stoichiometric ratio to the acetate anion.

[0028] After coating the acetate-containing solution, it is preferable to dry the carrier in air, diluted air, or in an inert gas at a temperature range of 70° C. to 120° C., more preferably 80° C. to 110° C., and most preferably 90° C. to 100° C. The drying time for the acetate-containing carrier is preferably in the range of 10 to 100 minutes, more preferably 30 to 60 minutes.

[0029] The drying of the acetate-containing carrier can be carried out in a conventional drying apparatus or in a coating apparatus. When drying is carried out in a coating apparatus, it is preferably carried out so that the carrier is in a stationary state therein, i.e., as they move. When using a moving bed or fluidized bed apparatus, the carrier is preferably not moved in the moving bed or fluidized bed during drying.

[0030] In step (b), the dissolved Pd precursor compound and the dissolved Au precursor compound are applied to a bed of catalyst support in a recirculating operation.

[0031] Examples of preferred Pd precursor compounds are water-soluble Pd salts. Particularly preferred are Pd precursor compounds selected from the group consisting of Pd(NH3)4(HCO3)2, Pd(NH3)4(HPO4), ammonium Pd oxalate, Pd oxalate, Pd(K2 oxalate)2, Pd(II) trifluoroacetate, Pd(NH3)4(OH)2, Pd(NO3)2, HPd(OAc)2(OH)2, Pd(NH3)2, Pd(NH3)4(NO3)2, HPd(NO2)4, Na2Pd(NO2)4, Pd(OAc)2 and freshly precipitated Pd(OH)NO2.

[0032] If freshly precipitated Pd(OH)2 is used, it is preferably prepared as follows: A 0.1% to 40% by weight aqueous solution is preferably prepared from palladium tetrachloride. Base is then added to this aqueous solution, preferably until a brown solid, i.e. Pd(OH)2, precipitates. The freshly precipitated Pd(OH)2 is isolated, washed, and dissolved in an alkaline aqueous solution to prepare the solution for application to the catalyst support.

[0033] The compound Pd(NH3)4(OH)2 is preferably prepared as follows: a precursor compound, for example Na2PdCl4, is precipitated with potassium hydroxide as described above to give palladium hydroxide and the precipitate, after filtration and washing, is dissolved in aqueous ammonia to give Pd(NH3)4(OH)2.

[0034] The preparation method according to the invention can also use a Pd nitrite compound. A preferred Pd nitrite precursor compound can be obtained, for example, by dissolving Pd(OAc)2 in a NaNO2 or KNO2 solution.

[0035] Examples of preferred Au precursor compounds are water-soluble Au salts. According to a particularly preferred embodiment of the method according to the invention, the Au precursor compounds are selected from the group consisting of KAuO2, NaAuO2, CsAuO2, NMe4AuO2, KAuCl4, (NH4)AuCl4, HAuCl4, KAu(NO2)4, NaAu(NO2)4, CsAu(NO2)4, KAu(OAc)3(OH), NaAu(OAc)3(OH), CsAu(OAc)3(OH), HAu(NO3)4 and Au(OAc)3. It is advantageous to precipitate the oxide / hydroxide from an acidic gold solution, wash and isolate the precipitate and dissolve it in acetic acid or KOH to prepare fresh Au(OAc)3 or KAuO2 in each case.

[0036] In the context of the present invention, dissolved Pd-containing and Au-containing precursor compounds are understood to be compounds which are present in dissolved form in a solvent, preferably water, an aqueous base or an aqueous acid.

[0037] In the present specification, salts are described as water-soluble if they are sufficiently soluble in water, aqueous base or aqueous acid.

[0038] The Pd precursor compound and the Au precursor compound are preferably selected so as to be free of catalyst poisons. After application of the noble metal compounds, the catalyst bodies are preferably simply dried, preferably in the same fluidized bed coating apparatus in which the application was carried out. The precursor compounds are particularly preferably substantially chloride-free.

[0039] Substantially chloride free means that the molecular formula of the compound does not contain chloride, but does not exclude the possibility that the compound may contain unavoidable chloride impurities, for example as a result of manufacture. The chloride content in substantially chloride free Pd and Au precursor compounds is a maximum of 125 ppm per weight % of Pd and Au in the precursor compounds.

[0040] The application of the Pd-containing precursor compound and the Au-containing precursor compound is carried out by sequential, i.e., consecutive, or simultaneous spray application of the dissolved Pd-containing precursor compound and the dissolved Au-containing precursor compound onto a bed of the catalyst support in a recirculating operation.

[0041] This coating can be performed by simultaneously coating a Pd-containing precursor compound solution and a Au-containing precursor compound solution, or by coating a Pd-containing precursor compound solution and a Au-containing precursor compound solution.

[0042] Alternatively, the coating may be performed sequentially, using a Pd-containing precursor compound solution in the first step and an Au-containing precursor compound solution in the second step, or using an Au-containing precursor compound solution in the first step and a Pd-containing precursor compound solution in the second step.

[0043] In one embodiment, when applied sequentially, the solution applied in the second step includes both a Pd-containing precursor compound and an Au-containing precursor compound.

[0044] If the shell catalyst contains several different catalytically active species in the shell, such as one or several active and promoting metals, the catalyst support shaped body may be subjected to the method according to the invention as many times as necessary.

[0045] Alternatively, the process according to the present invention can be carried out using a mixed solution containing different desired catalytically active species or their precursors. Furthermore, in the process according to the present invention, each solution of the catalytically active species or its precursor can be sprayed simultaneously onto the catalyst support.

[0046] The process gas used in the production method according to the invention is typically air. In further embodiments, it is possible to use an inert gas, such as nitrogen, methane, short-chain saturated hydrocarbons, a noble gas, preferably helium, neon or argon, or a halogenated hydrocarbon, or a mixture of two or more of these.

[0047] Heating the catalyst support in steps (a) and (b) of the first production method according to the invention makes it possible to control the width of the precious metal shell formed, since the diffusion of the precious metal into the support is reduced due to faster evaporation, depending on the temperature, of at least one solution, preferably an aqueous solution, applied in step b) in the case of combined application of Pd-containing and Au-containing precursor compounds, or faster evaporation of the solution, preferably an aqueous solution, applied first in step b) in the case of successive application of Pd-containing and Au-containing precursor compounds.

[0048] For example, at higher temperatures, the drying rate is higher and the solution in contact with the catalyst support dries quickly, so that the solution applied to the catalyst support does not penetrate deeply into the support, and therefore a thinner shell rich in active species can be obtained at higher temperatures.

[0049] Surprisingly, it has been found that in the first production method according to the invention, heating the catalyst support in step (a) to a temperature 5°C to 30°C, preferably 7°C to 25°C, most preferably 10°C to 20°C higher than the coating temperature or, in the case of sequential coatings, the temperature of the first coating in step (b), makes it possible to advantageously control the distribution of Pd, such that the maximum of the Pd concentration is within a range of 0 to 40 micrometers from the surface of the catalyst molding, palladium is present in a region of a shell thickness of 30 to 200 μm, and the half-width of the concentration distribution is 10 to 70 μm.

[0050] The temperature of the catalyst support set in steps (a) / (b) is controlled by measuring the exhaust temperature / bed temperature and, optionally, by additional control.

[0051] The temperature set in step (a) is in the range of 60°C to 120°C, preferably 65°C to 110°C, and particularly preferably 70°C to 100°C.

[0052] The coating temperature, or in the case of continuous coating, the initial coating temperature set in step (b) is in the range of 55°C to 115°C, preferably in the range of 55°C to 110°C, more preferably in the range of 60°C to 100°C, and particularly preferably in the range of 65°C to 90°C.

[0053] When applied sequentially, the second application can be performed at the same temperature as the first application, in one embodiment, the temperature during the second application is 5° C. to 30° C. higher than during the first application, preferably 5° C. to 20° C. higher, most preferably 5° C. to 10° C. higher.

[0054] The spraying of water in step (a) of the second manufacturing method according to the present invention can be controlled so that the width of the precious metal shell formed is comparable, because the water evaporates during contact with the catalyst support, resulting in a temporary temperature drop of the catalyst support that is re-corrected by the temperature control of the coating device, and the subsequent application of the metal-containing aqueous solution can be carried out at the desired temperature. Thus, the aqueous solution applied in step (b) can evaporate faster, or in the case of successive applications, the first applied solution can evaporate faster, reducing the diffusion of the precious metal into the support.

[0055] For example, at higher temperatures, the drying rate is higher and the solution in contact with the catalyst support dries quickly, so that the solution applied to the catalyst support does not penetrate deeply into the support, and therefore a thinner shell rich in active species can be obtained at higher temperatures.

[0056] The temperature of the catalyst support set in steps (a) / (b) is controlled by measuring the exhaust temperature / bed temperature and, optionally, by additional control.

[0057] The temperature set in step (a) is in the range of 55°C to 110°C, preferably 60°C to 100°C, and particularly preferably 65°C to 90°C.

[0058] The coating temperature, or in the case of continuous coating, the initial coating temperature set in step (b) is the same as in step (a) and is in the range of 55°C to 110°C, preferably 60°C to 100°C, particularly preferably 65°C to 90°C.

[0059] When applied sequentially, the second application can be performed at the same temperature as the first application, in one embodiment the temperature during the second application is 5°C to 30°C higher, preferably 5°C to 20°C higher, most preferably 5°C to 10°C higher.

[0060] In the production process according to the invention, drying of the catalyst support sprayed with the solution is preferably carried out continuously using a process gas.

[0061] In one embodiment of the method according to the present invention, the catalyst support is subjected to a fixing step after step (b) for fixing the catalytically active species or its precursor on the catalyst support. Suitable means include spraying a caustic solution onto the catalyst support carrying the precious metal compound or immersing the catalyst support in a solution containing a caustic solution.

[0062] This is followed by a water treatment to remove excess caustic from the catalyst support. This process is particularly suitable when the applied Pd or any Au precursor compounds contain components that act as catalyst poisons, such as the corresponding Pd or Au chlorides, especially in the production of VAM.

[0063] In a preferred embodiment, the catalyst support obtained after step (b) is heat treated at a temperature in the range of 300°C to 600°C, in particular for 1 hour to 6 hours, to convert the precursor compounds into the corresponding hydroxide compounds / oxides. In a further embodiment, the catalyst support obtained after step (b) is dried at a temperature in the range of 80°C to 200°C, preferably 100°C to 150°C.

[0064] In a further embodiment, the catalyst support obtained after step (b) is not subjected to a fixing step but is dried at a temperature ranging from 80°C to 200°C, preferably from 100°C to 150°C.

[0065] It is particularly preferred that neither drying nor heat treatment in the range of 300° C. to 600° C. is carried out after step (b) and before the reduction in step (c).

[0066] In one embodiment, step (b) is followed by step (c), which comprises heat treating the catalyst shaped body obtained after step (b) in a non-oxidizing atmosphere to reduce the metal components of the precursor compounds to elemental metals.

[0067] The reduction in step (c) can be carried out in the fluidized bed coater itself or in a separate reduction reactor. When the reduction is carried out in a fluidized bed coater, it is typically carried out using a mixture of 2% to 5% by volume of hydrogen and nitrogen at a temperature in the range of 70°C to 150°C, for example for 30 minutes to 5 hours.

[0068] If carried out in a separate reduction reactor, it is typically carried out using a mixture of 2% to 5% by volume hydrogen in nitrogen, e.g. forming gas, at a temperature preferably in the range of 70 to 500°C, for a period of 30 minutes to 5 hours.

[0069] Suitable further reducing agents include ethylene, CO, NH3, formaldehyde, methanol and hydrocarbons, where the reducing agent may also be diluted with an inert gas, such as carbon dioxide, nitrogen or argon. It is preferred to use a reducing agent diluted with an inert gas. It is preferred to use a mixture of hydrogen and nitrogen or argon, and the hydrogen content is preferably 1% to 15% by volume.

[0070] In a further embodiment, the reduction of the precious metal in a pure nitrogen atmosphere can be carried out at a temperature in the range of 130°C to 200°C, preferably in the range of 140°C to 170°C.

[0071] In a further embodiment, the reduction of the noble metal can also be carried out in the liquid phase, preferably with the reducing agents hydrazine, potassium formate, sodium formate, formic acid, H2O2, hypophosphorous acid or sodium hypophosphite.

[0072] The catalyst supports used in the manufacturing method according to the invention are of various shapes, such as tablets, cylinders, rings, irregular pellets or spheres. The catalyst supports are preferably spherical. The geometric shape allows for uniform rotation of the support about its axis in a recirculating operation, thus allowing the catalyst support to be uniformly impregnated with the catalytically active species solution. The catalyst supports used in the manufacturing method according to the invention are not powder-like materials.

[0073] Spherical catalyst supports have an arithmetic diameter in the range of 1 to 10 mm, preferably 3 to 9 mm, particularly preferably 3 to 8 mm. In the present specification, the term "spherical" is understood to include ellipsoids whose diameter along a pole-to-pole axis is smaller than the diameter along the corresponding equatorial axis. The ratio of the diameter along the pole-to-pole axis to the diameter along the equatorial axis is in the range of 0.9 to 1.0. The arithmetic diameter of these approximately spherical bodies is determined using the pole-to-pole diameter.

[0074] The catalyst support typically comprises a compound from the group of titanium oxide, silicon oxide, aluminum oxide, zirconium oxide, magnesium oxide, silicon carbide, magnesium silicate, zinc oxide, zeolites, layered silicates or mixtures thereof. The catalyst support preferably comprises a Si-Al mixed oxide, in particular a Si-Al mixed oxide in the form of a layered silicate, preferably a layered silicate in the form of calcined acid-treated bentonite.

[0075] The proportion of these compounds or mixtures is typically at least 70% by weight, preferably at least 80% by weight, particularly preferably at least 90% by weight, based on the weight of the catalyst support after loss on ignition. In a particularly preferred embodiment, the catalyst support comprises calcined acid-treated bentonite in a proportion of at least 70% by weight, preferably at least 80% by weight, particularly preferably at least 90% by weight, most preferably at least 95% by weight, based on the weight of the catalyst support after loss on ignition.

[0076] The term "natural layered silicates", also used synonymously in the literature as "phyllosilicates", refers to untreated or treated silicate minerals, derived from natural sources, that are tetrahedral structures of SiO4 and have the general formula [SiO2O5]. 2- In this layer, SiO4 tetrahedra are interconnected.

[0077] These tetrahedral layers are alternated with so-called octahedral layers, and cations, especially Al and Mg, are octahedrally surrounded by OH or O. For example, a distinction is made between two-layered and three-layered phyllosilicates. In the present specification, preferred layered silicates are clay minerals, especially kaolinite, beidellite, hectorite, saponite, nontronite, mica, vermiculite and smectite, with smectite and especially montmorillonite being particularly preferred. The definition of the term "layered silicates" can be found, for example, in "Lehrbuchderanorganischen Chemie", HollemannWiberg, deGruyter, deedition, 2007 (ISBN978-3-11-017770-1), or in "RoemppLexikonChemie" 10th edition, GeorgThiemeVerlag, under the term "phyllosilicates".

[0078] Typical treatment of the natural phyllosilicate carrier material before use includes, for example, treatment with acid and / or calcination.In the present invention, the natural layered silicate, particularly preferred, is bentonite.Bentonite is not a natural layered silicate in the strict sense, but rather a mixture mainly of clay minerals containing layered silicate.

[0079] When the natural layered silicate is bentonite, it is understood that the natural layered silicate is present in the catalyst support in the form of, or as a component of, calcined acid-treated bentonite.

[0080] Catalyst supports based on natural layered silicates, in particular on acid-treated calcined bentonite, in the form of shaped bodies can be produced, for example, as follows: an acid-treated (uncalcined) bentonite and water-containing mixture is shaped by compression using equipment well known to the person skilled in the art, for example an extruder or tablet press, to give shaped bodies, and the unhardened shaped bodies are subsequently calcined to give stable shaped bodies.

[0081] The specific surface area of ​​the catalyst support depends, inter alia, on the quality of the (raw) bentonite used, on the acid treatment process of the bentonite used, i.e., for example, the nature and amount of bentonite and the concentration of the inorganic acid used, the duration and temperature of the acid treatment, as well as on the pressing pressure, the calcination time, temperature and atmosphere.

[0082] Acid-treated bentonite can be obtained by treating bentonite with a strong acid, such as sulfuric acid, phosphoric acid or hydrochloric acid. The definition of the term bentonite, which is also applied in the present specification, is specified in Roempp, Lexikon Chemie, 10th edn., Georg Thieme Verlag. In the present invention, a particularly preferred bentonite is a natural aluminum-containing layered silicate containing montmorillonite as the main material. After the acid treatment, the bentonite is usually washed with water, dried and ground.

[0083] The BET surface area of ​​the catalyst support is 10 to 600 m 2 / g, preferably 20 to 400m 2 / g, particularly preferably 80 to 170m 2 / g. The BET surface area is determined by the one-point method by nitrogen adsorption in accordance with DIN 66132.

[0084] In one embodiment, the total pore volume of the catalyst support without being coated with the precursor compound is at least 0.1 ml / g, preferably at least 0.18 ml / g, more preferably at least 0.4 ml / g, measured according to DIN 66133 (Hg porosimetry). In a further embodiment, the total pore volume is in the range of 0.1 ml / g to 0.8 ml / g, preferably in the range of 0.18 ml / g to 0.6 ml / g, particularly preferably in the range of 0.35 to 0.55 ml / g.

[0085] The catalyst supports used in the process according to the invention have a hardness of at least 20N, preferably at least 30m, particularly preferably at least 40N and most preferably at least 50N.

[0086] The proportion of Pd in ​​the catalyst according to the present invention is in the range of 0.2% by weight to 2.0% by weight, preferably in the range of 0.4% by weight to 1.75% by weight, and particularly preferably in the range of 0.7% by weight to 1.5% by weight, based on the weight of the reduced catalyst molded body containing a precious metal after drying loss.

[0087] The proportion of Au in the catalyst according to the present invention is in the range of 0.1 to 1.2% by weight, preferably in the range of 0.2 to 1.0% by weight, and most preferably in the range of 0.3 to 0.8% by weight, based on the total weight of the catalyst molded body after reduction and drying loss.

[0088] In a preferred embodiment, the Au / Pd atomic ratio of the catalyst molded article according to the present invention is in the range of 0.01 to 1.2, preferably in the range of 0.05 to 1.0, more preferably in the range of 0.1 to 0.8, and particularly preferably in the range of 0.15 to 0.6.

[0089] The shell catalyst of the present invention preferably contains an alkali metal compound as promoter, preferably a compound of potassium, sodium, cesium or rubidium, particularly preferably a potassium compound. Suitable and particularly preferred potassium compounds include potassium acetate KOAc, potassium carbonate K2CO3, potassium bicarbonate KHCO3 and potassium hydroxide KOH, preferably potassium acetate KOAc.

[0090] The potassium compound can be applied to the catalyst support / catalyst compact either before or after reduction of the metal components to Pd and Au metals.

[0091] In a preferred embodiment, the potassium compound is applied before the application of the precious metal compound, particularly preferably before step (a).

[0092] In this case, care must be taken in subsequent steps such as application, fixation or reduction of the precursor compounds that the heat treatment is carried out only if the potassium compound is not or only slightly decomposed to its oxide, since potassium oxide is only slightly converted to potassium acetate under the reaction conditions of the VAM reaction.

[0093] The catalyst support / catalyst shaped body is preferably only exposed to temperatures below 200°C.

[0094] When the catalyst shaped body according to the invention contains an alkali metal acetate, preferably potassium acetate, the amount of the alkali metal acetate in the catalyst bed is 0.1 to 0.7 mol / l, preferably 0.3 to 0.5 mol / l.

[0095] In a preferred embodiment, the catalyst molded body of the present invention has an alkali metal / Pd atomic ratio in the range of 1 to 16, more preferably in the range of 2 to 13, and particularly preferably in the range of 3 to 10. Preferably, the lower the alkali metal / Pd atomic ratio, the smaller the surface area of ​​the catalyst molded body.

[0096] Considering low pore diffusion limitations, in a further preferred embodiment of the Pd / Au catalyst according to the present invention, the catalyst molding may have an average pore diameter of 8-50 nm, preferably 10-35 nm, preferably 11-30 nm.

[0097] The acidity of the catalyst shaped bodies can have an advantageous effect on the activity of the catalyst according to the invention. In a further preferred embodiment of the catalyst according to the invention, the catalyst shaped bodies have an acidity in the range from 1 to 150 μval / g, preferably in the range from 5 to 130 μval / g, particularly preferably in the range from 10 to 100 μval / g.

[0098] The acidity of the shaped catalyst bodies is determined as follows: 1 g of finely ground shaped catalyst bodies is mixed with 100 ml of water (with a pH blank value) and extracted for 15 minutes while stirring.

[0099] The mixture is then titrated with 0.01 n NaOH solution to at least pH 7.0. The titration involves first dripping 1 ml of NaOH solution into the extract (1 drop / sec), then waiting 2 minutes, reading the pH, dripping another 1 ml of NaOH, etc. Determine the blank value of the water used and correct the acidity calculations accordingly.

[0100] A titration curve (0.01 ml NaOH vs. pH) is then plotted and the intercept of the titration curve at pH 7 is determined. The molar equivalent is calculated at 10-6 equiv / g of carrier and is obtained from the NaOH consumption at the intercept at pH 7.

[0101]

number

[0102] The shell catalyst is preferably spherical or substantially spherical. The spheres have a diameter in the range from 1 to 10 mm, preferably from 3 to 9 mm, particularly preferably from 3 to 8 mm.

[0103] In order to enhance the activity of the Pd / Au catalyst according to the present invention, the catalyst molded body can be doped with at least one oxide of a metal selected from the group consisting of Zr, Hf, Ti, Nb, Ta, W, Mg, Re, Y and Fe, preferably ZrO2, HfO2 or Fe2O3. The proportion of the doped oxide in the catalyst molded body is preferably 0.1% to 20% by weight, preferably 1.0% to 18% by weight, preferably 4% to 16% by weight, based on the weight of the catalyst molded body.

[0104] In a further preferred embodiment of the catalyst molded body according to the present invention, the water absorption rate of the catalyst molded body is 40% to 75%, preferably 50% to 70%, calculated as the weight increase due to water absorption.

[0105] The water absorption is determined by soaking 10 g of catalyst molding with deionized water for 30 minutes until no more air bubbles emerge from the sample. The excess water is then drained off and the soaked sample is gently wiped dry with a cotton cloth to remove any adhering water from the sample. The hydrous catalyst molding is then weighed and the absorption rate is calculated according to the following formula: (Final weight (g) - Initial weight (g)) x 10 = Water absorption capacity (%)

[0106] The BET surface area of ​​the shell catalyst is 10 to 600 m 2 / g, preferably 20 to 400m 2 / g, particularly preferably 80 to 170m 2 / g. The BET surface area is determined by the one-point method by nitrogen adsorption in accordance with DIN 66132.

[0107] In one embodiment, the total pore volume of the shell catalyst without coating with precursor compound is at least 0.1 ml / g, preferably at least 0.18 ml / g, more preferably at least 0.4 ml / g, measured according to DIN 66133 (Hg porosimetry). In a further embodiment, the total pore volume is in the range of 0.1 ml / g to 0.8 ml / g, preferably in the range of 0.18 ml / g to 0.6 ml / g, particularly preferably in the range of 0.35 to 0.55 ml / g.

[0108] The shell catalyst has a hardness of at least 20N, preferably at least 30m, particularly preferably at least 40N and most preferably at least 50N.

[0109] In a further preferred embodiment of the catalyst shaped body according to the invention, at least 80%, preferably at least 85%, preferably at least 90% of the total pore volume of the catalyst shaped body may be formed by mesopores and macropores.

[0110] This prevents a decrease in the activity of the catalyst bodies according to the invention resulting from diffusion limitations, particularly in the case of a relatively thick shell.The terms micropores, mesopores and macropores are understood to mean pores with a diameter of less than 2 nm, a diameter in the range from 2 to 50 nm and a diameter of more than 50 nm, respectively.

[0111] The invention further relates to a process for the preparation of alkenyl carboxylic esters, in particular VAM or allyl acetate monomers, with the aid of the shell catalyst according to the invention, which process for the preparation of VAM is carried out by passing acetic acid, ethylene and oxygen or an oxygen-containing gas through the catalyst shaped body according to the invention.

[0112] This is generally carried out by passing a gas containing acetic acid, ethylene and oxygen or an oxygen-containing gas through the catalyst shaped body according to the invention at a temperature in the range of 100°C to 200°C, preferably in the range of 120°C to 200°C, and at a pressure in the range of 1 to 25 bar, preferably in the range of 1 to 20 bar, where unconverted reactants can be recycled.

[0113] The oxygen concentration is advantageously kept below 10% by volume. However, dilution with an inert gas such as nitrogen or carbon dioxide may also be advantageous. Carbon dioxide is particularly suitable for dilution, since it is formed in small amounts in the course of the VAM synthesis and accumulates in the circulation gas.

[0114] The vinyl acetate obtained is isolated using a suitable method, for example as described in US 5,066,365A. A similar process has also been disclosed for allyl acetate. It is also known that in such a vinyl acetate production process, the promoter that may be present in the catalyst, for example potassium acetate KOAc, can be added later to resupply the promoter lost during the use of the catalyst in the production process.

[0115] This can also be carried out during the course of the process for the production of alkenyl carboxylic acid esters, so that the promoter acetate compound is mixed with the acetic acid and / or potassium acetate fed to the process or is metered in separately.

[0116] The present invention will now be described in more detail with reference to a number of examples, which are not to be construed as limiting in any way.

[0117] FIG. 1 shows experimental data points for Pd concentration and x for Catalyst 1 of the embodiment. surface After the measurement, a plot of the sigmoid function determined by the same measurement method that determined the starting point of the geometric surface is shown.

[0118] FIG. 2 shows a plot of the experimental data points of Pd concentration and the curve for catalyst 1 obtained using an appropriate fit function.

[0119] FIG. 3 shows a plot of the experimental data points of Pd concentration and the curve for catalyst 2 obtained using an appropriate fit function.

[0120] FIG. 4 shows a plot of the experimental data points of Pd concentration and the curve for catalyst 3 obtained using an appropriate fit function.

[0121] FIG. 5 shows the curves for catalysts 1, 2 and 3 obtained using the appropriate fitting functions.

[0122] FIG. 6 shows the plot of selectivity at different space-time yields and their trend lines for catalysts 1 and 2 in the reaction of acetic acid, ethylene and oxygen to give vinyl acetate monomer. EXAMPLES

[0123] Measurement method Pore ​​volume: The pore volume was measured by the mercury porosimetry method according to DIN 66133 in the pressure range 1-2000 bar. BET surface area: The BET surface area was determined according to DIN 66135. To determine the micropore volume and the micropore surface area, the adsorption isotherms of nitrogen at liquid nitrogen temperature (77 K) were measured using a Micromeritics ASAP2020M instrument.

[0124] Elemental distribution in the support: The distribution of Pd and Au in the catalyst bodies was determined by cutting the support in half to produce a cross section of the spherical catalyst body. This made it possible to determine the spatial distribution of the metals using EDX spectroscopy (Energy Dispersive X-ray), also known as EDX spectroscopy (energy dispersive X-ray diffraction), with the aid of an electron microscope. A measuring head sensitive to Pd was moved across the sample, making it possible to determine its respective distribution along a line from the outer surface towards the centre of the catalyst body.

[0125] The measurements were performed using a LEO1530 electron microscope coupled to a Quantax EDX unit with a Bruker XFlash4010 detector. The measurement conditions were as follows: Accelerating voltage (EHT): 20 kV Opening: 120μm Distance used: Approx. 16 mm (optimal for SEM-EDX shape) SEM detector: SE2 Magnification: Low (e.g. 55x) Measurement time: 10 to 15 minutes

[0126] The starting point of the measurement was set at least 80 μm from the outer edge of the sample and measurements were made from there towards the centre of the sphere, the length of the measurement line was 1600 μm.

[0127] Measurements of various catalyst shapes are typically performed such that the starting point of the measurement is set at least 80 μm from the beginning of the geometric surface of the sample, from which the sample head is moved vertically towards the original geometric surface of the sample and then moved over the sample.

[0128] This allowed the determination of the shell thickness of Pd, whose inner end was defined as the point where the intensity was first smaller than the sum of the bremsstrahlung radiation and had a value three times its standard deviation.

[0129] The beginning of the geometric surface of the measured catalyst molding was determined by fitting the following function to the bremsstrahlung intensity inside and outside the catalyst molding along the measurement line at various points x:

[0130]

number

[0131] rate is a measure of the gradient at the inflection point, base corresponds to the bremsstrahlung intensity I outside the catalyst molding, and max corresponds to the bremsstrahlung intensity I in the region inside the catalyst molding that does not contain precious metal, i.e., outside the precious metal shell region.

[0132] The inflection point x0 of this sigmoid function determines the outer edge of the shell, and to determine the concentration distribution of the precious metal along the subsequent measurement line, the value of x0 is subtracted from the measurement x, and all series of measurements are taken at the point x on the outer surface. surface = Starts at 0 μm.

[0133] FIG. 1 shows the measured intensity and x for the catalyst 1 of the embodiment. surface After measuring, a graph of the sigmoid function defined by the same method as for defining the start of the geometric surface is shown.

[0134] This ensures that a sufficient number of catalyst bodies are individually measured and their outer surface is defined.

[0135] The concentration distribution of the palladium precious metal along the line was determined by calculating the arithmetic mean of the intensities at the x points from the individual measurements and fitting the precious metal concentration distribution from the resulting measurements with the following Gaussian function:

[0136]

number

[0137] x max = Position of peak maximum Determine A = peak height max = Determine the asymmetry of the concentration distribution rate=Determine the asymmetry of the concentration distribution

[0138] Each value of the half-width of the Pd concentration distribution can also be determined as follows, where the half-width is the difference between two points along the measurement line at half the maximum intensity: the left value of the half-width is therefore the difference between the first point on the measurement line having half the maximum intensity value and the point having the maximum intensity value, and the right value of the half-width is the difference between the point having the maximum intensity value and the second point on the measurement line having half the maximum intensity value.

[0139] Measurement of elemental concentrations: The elemental concentrations were determined by dokimastic digestion by copper cupration followed by ICP-AES analysis and calculated based on the catalyst bodies after drying at 120° C. for 2 hours.

[0140] Measurement of hardness: The hardness of the catalyst molded body was determined as the average value of 99 catalyst molded bodies using a Dr. Schleuniger Pharmatron AG8M tablet hardness tester. Before the measurement, the catalyst molded body was dried at 130° C. for 2 hours. The instrument settings were as follows: Hardness:N Distance to catalyst compact: 5.00mm Delay time: 0.80 seconds Feed Type: 6D Speed: 0.60mm / sec

[0141] The following examples are intended to illustrate the invention.

[0142] Example 1: Catalyst 1 100 g of bentonite-containing catalyst support KA-160 (available from Clariant) was weighed and impregnated with a mixture of 39.3 g of 2 molar KOAc solution and 18.1 g of deionized water according to the pore-filling method (incipient wetness).

[0143] After static drying in a fluidized bed dryer at 90°C for 35 minutes, the mixture was cooled to room temperature and transferred to a coating device InnojetIAC025. The KOAc-impregnated support was operated in a fluidized bed using process gas. Then, 36.8g of deionized water was sprayed onto the catalyst support at a spray rate of 4g / min. The process air was temperature controlled at 70°C.

[0144] Subsequently, 7.0 g of an aqueous cesium gold oxide solution (4.7 wt % Au) was diluted with deionized water to give 50 g of coating solution, which was applied to the catalyst support in a coating apparatus in a first coating step at a spray rate of 4 g / min and a process air temperature of 70°C.

[0145] Subsequently, in the second coating step, 2.7 g of aqueous cesium goldate solution (4.7 wt % Au) and 38.9 g of tetraamine palladium hydroxide solution (3.4 wt % Pd) were diluted with deionized water to give 80 g of coating solution, which was applied to the catalyst support at a spray rate of 4 g / min and a process air temperature of 70°C.

[0146] The catalyst support was kept in a fluidized bed. After further static drying in a fluidized bed dryer (90°C / 35 min), the catalyst molded body was statically reduced in a tubular furnace with forming gas (2% H2 in N2) at 100°C for 45 min.

[0147] Elemental analysis of the catalyst molded body revealed the following proportions: Pd: 1.3% by weight Au: 0.46% by weight

[0148] The precious metal distribution was measured using a Bruker AXS LEO 1530 scanning electron microscope equipped with an energy dispersive spectrometer. To measure the precious metal concentration through the shell thickness, the catalyst bodies were cut and glued onto aluminum sample holders followed by carbon deposition.

[0149] The detector used was a nitrogen-free silicon drift chamber detector with an energy resolution of 125 eV for manganese K-alpha radiation, XFlash® 410. The following parameters were used for the measurements:

[0150] Scan resolution: 500 dots Data point spacing: 1.8μm Magnification: 200x Beam voltage: 20kV Beam current: 20nA Input pulse rate: 50000 pulses / sec Line scan measurement time: 200 seconds

[0151] The shell thickness of ten spheres of the shell catalyst prepared as above was measured.

[0152] The maximum Pd concentration was 23 micrometers below the geometric surface of the shell catalyst. The shell thickness of Pd was 130 micrometers and that of Au was 93 micrometers.

[0153] The half-width of Pd was 60 micrometers, the value on the left side of the half-width was 16 micrometers, and the value on the right side of the half-width was 44 micrometers. The ratio of the value on the left side of the half-width to the value on the right side of the half-width was 0.37. The Pd concentration curve is shown in FIG. 2.

[0154] Example 2: Catalyst 2 100 g of bentonite-containing catalyst support material KA-160 (available from Clariant) was weighed and impregnated with a mixture of 39.3 g of 2 molar KOAc solution and 18.1 g of deionized water according to the pore-filling method (incipient wetness). After static drying in a fluidized bed dryer at 90° C. for 35 minutes, the mixture was cooled to room temperature and transferred to a coating device Innojet IAC025.

[0155] The KOAc-impregnated support was operated in a fluidized bed using process gas. The process air was temperature-controlled at a temperature of 90°C and held for 2 minutes before starting the spray application of the cesium aurate solution. 7.0 g of the cesium aurate solution (4.7 wt% Au) was diluted with deionized water to make 50 g of coating solution, which was applied to the catalyst support in the coating device at a spray rate of 4 g / min in the first coating step, and the temperature of the process air was lowered from 90°C by 15°C upon the start of the spray operation, and the process air was further actively lowered to 70°C and then maintained at this temperature.

[0156] Subsequently, in the second coating step, a mixture of 2.4 g of cesium aurate aqueous solution (4.7 wt % Au) and 38.9 g of tetraamine palladium hydroxide solution (3.4 wt % Pd) was diluted with deionized water to obtain 80 g of coating solution, which was applied to the catalyst support at a spray rate of 4 g / min and a process air temperature of 70°C.

[0157] The catalyst support was kept in a fluidized bed. After further static drying in a fluidized bed dryer (90°C / 35 min), the catalyst molded body was statically reduced in a tubular furnace with forming gas (2% H2 in N2) at 100°C for 45 min.

[0158] Elemental analysis of the catalyst bodies showed the following proportions: Pd: 1.3% by weight Au: 0.43% by weight

[0159] The precious metal distribution was measured as in Example 1. The maximum value of the Pd concentration was 30 micrometers below the geometric macroscopic surface of the shell catalyst. The shell thickness of Pd was 129 micrometers. The half-width of Pd was 50 micrometers. The value on the left side of the half-width was 16 micrometers and the value on the right side of the half-width was 34 micrometers. The ratio of the value on the left side of the half-width to the value on the right side of the half-width was 0.45. The Pd concentration curve is shown in FIG. 3.

[0160] Comparative Example 1: Catalyst 3 100 g of bentonite-containing support material KA-160 (available from Clariant) was weighed and impregnated with a mixture of 39.3 g of 2 molar KOAc solution and 18.1 g of deionized water according to the pore-filling method (incipient wetness).

[0161] After drying in a fluidized bed dryer at 90° C. for 35 minutes, the mixture was cooled to room temperature and transferred to a coating device, Innojet IAC 025. Using process gas, the KOAc-impregnated support was operated in a fluidized bed, heated to 70° C., and maintained for 2 minutes, and then sprayed with an aqueous solution of cesium laurate.

[0162] The spray coating was carried out by diluting 7.0 g of aqueous cesium gold oxide solution (4.7 wt% Au) with deionized water to obtain 50 g of coating solution, which was applied to the catalyst support in the first coating step at a spray rate of 4 g / min in a coating apparatus. The temperature of the process air was reduced by 15°C, but was then increased to 71°C and maintained at that temperature.

[0163] Subsequently, in the second coating step, a mixture of 2.4 g of cesium aurate aqueous solution (4.7 wt % Au) and 38.9 g of tetraamine palladium hydroxide solution (3.4 wt % Pd) was diluted with deionized water to obtain 80 g of coating solution, which was applied to the catalyst support at a spray rate of 4 g / min and a process air temperature of 70°C.

[0164] The catalyst support remains in the fluidized bed. After further static drying in a fluidized bed dryer (90°C / 35 min), the catalyst was statically reduced in a tube furnace with forming gas (2% H2 in N2) at 100°C for 45 min.

[0165] Elemental analysis of the catalyst showed the following proportions: Pd: 1.3% by weight Au: 0.43% by weight

[0166] The measurement of the precious metal distribution was carried out as in Example 1. The maximum value of the Pd concentration was 43 micrometers below the surface of the shell catalyst. The shell thickness of Pd was 183 micrometers. The half-width of Pd was 73 micrometers. The value on the left side of the half-width was 27 micrometers, and the value on the right side of the half-width was 46 micrometers. The ratio of the value on the left side of the half-width to the value on the right side of the half-width was 0.60. The Pd concentration curve is shown in FIG. 4.

[0167] Example 3: Reactor Testing Test results for catalysts 1, 2 and 3 regarding activity, selectivity and yield in vinyl acetate monomer synthesis

[0168] For the catalytic tests, 2.9 g of each catalyst was loaded into a reactor of 5.7 ml volume and then heated under inert gas to 138° C. At this temperature, the inert gas stream was replaced by a stream of acetic acid, ethylene and oxygen, which was passed through the reactor. At regular intervals, downstream of the reactor, samples of the effluent stream were taken and analyzed by gas chromatography.

[0169] After 24 hours reaction time at 138°C, the reactor temperature was increased to 140°C and maintained for a further 12 hours. It was then further increased to 142°C, 144°C, 146°C and finally back to 140°C. The reaction time for each was 12 hours and the pressure was 5-6 barg. The components used were 45% ethylene, 6% O2, 0.9% CO2, 9% methane, 15.5% acetic acid, balance N2.

[0170] Table 1 and Figure 6 show the selectivity / activity as a function of O2 conversion for catalysts 1, 2 and 3. Catalysts 1 and 2 made according to the invention clearly have much higher activity, selectivity (at the same activity level) and yield than comparative catalyst 3. This is also evident in Figure 6, which shows a plot of the selectivity of VAM as a function of space-time yield.

[0171] [Table 1]

Claims

1. A shell catalyst comprising Pd and Au, characterized in that it has a palladium concentration profile in the shell catalyst, the concentration profile conforming to an asymmetric Gaussian distribution, the maximum value of the palladium concentration being within a range of 0 to 40 micrometers from the geometric macroscopic surface of the catalyst body, the palladium being present in a region of a shell thickness of 30 to 200 μm, the half-width of the concentration distribution being 10 to 70 μm, and the ratio of the value on the left side of the half-width to the value on the right side of the half-width being 0.05 to 0.

55.

2. 2. The shell catalyst according to claim 1, wherein the maximum value of the Pd concentration is in the range from 5 to 40 micrometers, preferably from 5 to 35 micrometers, particularly preferably from 5 to 30 micrometers from the surface of the shell catalyst.

3. 3. The shell catalyst according to claim 1 or 2, wherein the Pd-containing shell has a thickness of 30 to 200 micrometers, preferably 40 to 180 micrometers, particularly preferably 50 to 160 micrometers, most preferably 60 to 140 micrometers.

4. The shell catalyst according to any of claims 1 to 3, further comprising an alkali metal acetate, preferably potassium acetate.

5. 5. Shell catalyst according to claim 1, wherein the proportion of Pd is in the range of 0.2% to 2.0% by weight, preferably in the range of 0.4% to 1.75% by weight and particularly preferably in the range of 0.7% to 1.5% by weight, and the proportion of Au is in the range of 0.1% to 1.2% by weight, preferably in the range of 0.2% to 1.0% by weight and most preferably in the range of 0.3% to 0.8% by weight, in each case based on the total weight of the catalyst shaped body after reduction and drying loss.

6. (a) subjecting a catalyst support bed to a recycle operation, wherein the bed is heated to a temperature of from 60° C. to 120° C. before or after the bed is subjected to the recycle operation; (b) applying dissolved Pd-containing precursor compound and dissolved Au-containing precursor compound by spraying, either sequentially or simultaneously, to the recirculating catalyst support bed, where if applied simultaneously, the temperature is 5° C. to 30° C., preferably 7° C. to 25° C., most preferably 10° C. to 20° C. lower than that in step (a), and where if applied sequentially, the temperature of the first application is 5° C. to 30° C., preferably 7° C. to 25° C., most preferably 10° C. to 20° C. lower than that in step (a); A method for producing a shell catalyst comprising Pd and Au according to any one of claims 1 to 5, comprising:

7. 7. The method according to claim 6, further comprising the step (c) of reducing the metal components of the precursor compound to elemental metals by heat treating the catalyst support obtained in step (b) in a non-oxidizing atmosphere after step (b).

8. 8. The process according to claim 6 or 7, wherein the coating temperature or, in case of successive coatings, the first coating temperature in step (b) is in the range of 55°C to 115°C, preferably in the range of 55°C to 110°C, more preferably in the range of 60°C to 100°C, particularly preferably in the range of 65°C to 90°C.

9. The method according to any one of claims 6 to 8, wherein in step (b), a dissolved Au-containing precursor compound is applied in a first step, and a dissolved Pd-containing precursor compound is applied in a second step.

10. A method according to any of claims 6 to 9, wherein an acetate salt is applied to the catalyst support prior to application of the Pd-containing precursor compound and the Au-containing precursor compound, preferably prior to step (a).

11. (a) operating a catalyst support bed in a recirculating manner to contact the bed with atomized water by spraying at a temperature in the range of 55°C to 110°C; (b) spraying a dissolved Pd-containing precursor compound and a dissolved Au-containing precursor compound onto the recirculating catalyst support bed, either sequentially or simultaneously, where the temperature is the same as in step (a) for simultaneous application and the temperature of the first application is the same as in step (a) for sequential application; A method for producing a shell catalyst comprising Pd and Au according to any one of claims 1 to 5, comprising:

12. 12. The method according to claim 11, further comprising, after step (b), a step (c) of reducing the metal components of the precursor compound to elemental metals by heat treating the catalyst support obtained in step (b) in a non-oxidizing atmosphere.

13. 13. The method according to claim 11 or 12, wherein in step (b), in a first step, a dissolved Au-containing precursor compound is applied, and in a second step, a dissolved Pd-containing precursor compound is applied.

14. A method according to any of claims 11 to 13, wherein an acetate salt is applied to the catalyst support prior to application of the Pd-containing precursor compound and the Au-containing precursor compound, preferably prior to step (a).

15. A process for the preparation of alkenyl carboxylic acid esters, in particular VAM or allyl acetate monomers, using a shell catalyst according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Sakusanbiniruno seizohoho

    JP1976004118A

  • Catalyst composition and its manufacturing method

    JP2002045706A

  • Method for producing a shell catalyst and the shell catalyst therefor

    JP2010527777A

  • Pre-impregnation of shell catalyst using acetate

    JP2014012268A

  • Layered support material for catalysts

    WO2005065821A1